The determinants of domestic saving in Kenya - Rodgers Musamali; Cecilia Mutia; Rose W. Ngugi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
The savings-growth nexus is widely acknowledged, both in policy and in the literature. But Kenya's numerous policy initiatives to encourage savings mobilization are yet to yield the expected outcomes. This paper identifies the key drivers of domestic saving in Kenya, exploiting fintech as an alternative channel for savings mobilization, and drawing lessons from the Kenyan experience so far. Using data from various sources, and employing an autoregressive distributive lag estimation model, we find that in the long run, private saving is positively and significantly influenced by the per capita income growth rate, inflation, and age dependency ratio, and negatively influenced by the public saving rate and terms of trade. National saving is positively and significantly influenced by the per capita income growth rate, inflation, and private sector credit growth rates in the long run. Wealth and deposit rates negatively influence national saving. Based on these findings, we recommend the following interventions to grow savings in Kenya: creating decent employment opportunities to enhance income growth; providing sustained financial development with a focus on savings mobilization; creating an enabling environment for the private sector; taking advantage of Kenya's young population; exploiting mobile money platforms to boost savings. Moreover, households show targeted saving behaviour where they accumulate financial savings and then transform them into savings in kind. Therefore, accounting for savings should go beyond the traditional focus on bank deposits and incorporate savings held in other forms. Households also use non-formal platforms for saving, and we suggest that existing barriers to formal saving platforms be removed to direct more saving into formal channels.
Keywords: C32; E21; H5; O3; 330; domestic saving; growth; policy; fintech; autoregressive distributive lag; Kenya